A benchmark model for contrasting test performance using macro and micro perspectives - Caintic, Helen Evangelista (2005)
The study sought to develop a benchmark model for contrasting test performance in a science aptitude test using macro and micro perspectives. The research was motivated by the phenomenal performance of some elementary schools in the Philippine Science High School National Competitive Examination over many years. It made use of the analytical survey design that follows a correlational strategy. Six top-performing elementary schools and six low-performing elementary schools composed the sample. The Instructional Practices Inventory was administered to the teachers, the Learning Environment Scale to the students, and the School Policies and Practices Checklist for Educators to the administrators. This study identified the best education practices in the said top-performing elementary schools in a science aptitude test.